ANALISIS KORELASI KEMAMPUAN KEUANGAN DAERAH DENGAN PERTUMBUHAN EKONOMI KABUPATEN SUMBAWA TAHUN 2018-2022 - Binar Dwiyanto Pamungkas; Fathona Harisma (Jurnal Ekonomi & Bisnis, 2025)
This study aims to analyze the correlation between regional financial capacity and economic growth in Sumbawa District in 2018-2022. The type of this study was associative. The type of data used was quantitative data. The type of data used was quantitative data obtained from secondary sources using documentation techniques. Documentation techniques were used to collect data from documents or archives held by the Central Statistics Agency regarding the Fiscal Decentralization Ratio and GRDP of Sumbawa District for 2018-2022. The collected of data was processed using statistical processing software Statistical Package for The Social Science (SPSS) to be analyzed using simple linear regression analysis techniques, partial hypothesis testing (t-test), and determinant coefficient testing (R2). Based on the results of data analysis, it can be concluded that regional finances do not effect economic growth in Sumbawa District in 2018-2022. The ability of the regional financial capacity to effect on the economic growth in Sumbawa District was 26,6%, while the remaining of 73,4% was effected by other variables outside this research model, such as per capita income inequality, employment and unemployment, changes in economic structure, capital accumulation, population growth, and technological progress.